Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations 62 HEALTH AND CLEANLINESS ness and its importance has been given with sincerity, it will be tested thoroughly on such occasions as these. On every occasion on which the teacher says, in respect of a breach of cleanliness, "It doesn't matter," he runs the risk of destroying all that he has painstakingly attempted to do in the course of his lessons. If he has insisted that cleanliness is a matter of the first importance, he must insist, when framing regulations for the conduct of an outdoor excursion, that pupils shall recognise it, by their behaviour, as a matter of the first importance. Anything less than this is a negation of his teaching. In framing this syllabus, and in drawing up the notes on method which accompany it, it has been our aim to show that the teaching of cleanliness is a simple matter; but at the same time it has not been forgotten that it is an arduous matter. It is very different from the teaching of a subject — if there be one — which has no relation to life, to habits, and to attitudes, but which is a mere matter of remembering facts for examination purposes. The teacher who endeavours to inculcate an attitude must himself take up that attitude. The teacher who endeavours to train his pupils to certain habits must possess those habits himself. The teacher who endeavours to teach cleanliness in the proper spirit must believe, with the Health and Cleanliness Council, that cleanliness is the first law of health, that it is necessary to individual and communal well-being, and that — Where there's Dirt there's Danger. 177/5/8/3